2020
DOI: 10.1098/rspb.2019.3001
|View full text |Cite
|
Sign up to set email alerts
|

Tropical seagrass Halophila stipulacea shifts thermal tolerance during Mediterranean invasion

Abstract: Exotic species often face new environmental conditions that are different from those that they are adapted to. The tropical seagrass Halophila stipulacea is a Lessepsian migrant that colonized the Mediterranean Sea around 100 years ago, where at present the minimum seawater temperature is cooler than in its native range in the Red Sea. Here, we tested if the temperature range in which H. stipulacea can exist is conserved within the species or if the exotic popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
44
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 57 publications
4
44
1
Order By: Relevance
“…The SDMs pointed out that maximum annual temperatures, and to a lesser degree maximum annual salinity, are essential factors determining the fundamental niche of H. stipulacea in the Mediterranean Sea. Our results are consistent with recent experimental studies demonstrating the first evidence of optimal acclimatization of native and invasive Mediterranean populations of H. stipulacea to projected scenarios of Mediterranean climate change, including temperatures of 30-32 • C and salinities higher than 40 PSU (Georgiou et al, 2016;Oscar et al, 2018;Nguyen et al, 2020;Wesselmann et al, 2020). Similarly, native populations from the Persian Gulf are adapted to even more extreme conditions, with in situ summer temperatures of 33-34 • C and summer salinities of 39.0-39.5 PSU (Tyberghein et al, 2012), defining H. stipulacea as an exceptional euryhaline and thermal-tolerant species.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The SDMs pointed out that maximum annual temperatures, and to a lesser degree maximum annual salinity, are essential factors determining the fundamental niche of H. stipulacea in the Mediterranean Sea. Our results are consistent with recent experimental studies demonstrating the first evidence of optimal acclimatization of native and invasive Mediterranean populations of H. stipulacea to projected scenarios of Mediterranean climate change, including temperatures of 30-32 • C and salinities higher than 40 PSU (Georgiou et al, 2016;Oscar et al, 2018;Nguyen et al, 2020;Wesselmann et al, 2020). Similarly, native populations from the Persian Gulf are adapted to even more extreme conditions, with in situ summer temperatures of 33-34 • C and summer salinities of 39.0-39.5 PSU (Tyberghein et al, 2012), defining H. stipulacea as an exceptional euryhaline and thermal-tolerant species.…”
Section: Discussionsupporting
confidence: 92%
“…While the presence of cold waters may represent a barrier to the expansion of H. stipulacea into westernmost habitats in the Mediterranean Sea, a recent study identified this region as a habitat refuge for the foundation species P. oceanica and C. nodosa under future climate scenarios (Chefaoui et al, 2018). Similarly, an even newer study reported that H. stipulacea in the Mediterranean Sea can cope with significantly lower temperatures (∼14 • C) than what observed in its native habitats (∼23 • C), suggesting a thermal niche shift to the lower temperatures in the Mediterranean Sea and potentially allowing this species to colonize temperate regions (Nguyen et al, 2020;Wesselmann et al, 2020). This physiological capability may be explained by the capacity to produce and accumulate high levels of unsaturation in the lipidic structures of the leaves of H. stipulacea (Beca-Carretero et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Shorter IL, as a proxy of higher shoot and root density, is a common feature under stressful environmental factors, suggesting that H. stipulacea invests excess energy (increased Alpha values) in increasing number of shoots ( Jensen and Bell, 2001 ; Kilminster et al, 2008 ) rather than on leaf length. In the literature, H. stipulacea thermal optima and limits showed differences between populations ( Nguyen et al, 2020 ; Wesselmann et al, 2020 ) but thermal optima at the Red Sea was set at 30°C ( Anton et al, 2020 ; Wesselmann et al, 2020 ). It is possible that these differences highlight the importance of the different population responses in coping with stressors ( McMillan and Phillips, 1979 ; Winters et al, 2011 ; Nguyen et al, 2020 ; Wesselmann et al, 2020 ) where other environmental factors, such as light irradiance, or population genetics influence the responses ( Collier et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…H. stipulacea , contrary to the large blades species, did not appear to be negatively affected by the studied factors, showing potentially a dormancy strategy under the different treatments. Even though performance differences have been observed between individuals from its native and invasive ranges ( Nguyen et al, 2020 ; Wesselmann et al, 2020 ) this species is generally recognized to be tolerant to a wide range of trophic conditions and temperatures ( Winters et al, 2020 ). Although H. stipulacea is considered as invasive in the Mediterranean and Caribbean Seas, there is no evidence of competition and displacement of native species in these areas ( Boudouresque et al, 2009 ; Al-Rousan et al, 2011 ; Gambi et al, 2018 ; Apostolaki et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%